Effect of Nocturnal Oxygen Therapy on Daytime Pulmonary Hemodynamics in Patients With Chronic Obstructive Pulmonary Disease Traveling to Altitude: A Randomized Controlled Trial - Lichtblau, Mona; Latshang, Tsogyal D.; Aeschbacher, Sayaka S.; Huber, Fabienne; Scheiwiller, Philipp M.; Ulrich, Stefanie; Schneider, Simon R.; Hasler, Elisabeth D.; Furian, Michael; Bloch, Konrad E.; Saxer, Stéphanie; Ulrich, Silvia (Frontiers in Physiology, 2021)
Introduction: We investigated whether nocturnal oxygen therapy (NOT) mitigates the increase of pulmonary artery pressure in patients during daytime with chronic obstructive pulmonary disease (COPD) traveling to altitude. Methods: Patients with COPD living below 800m, underwent examinations at 490m and during 2 sojourns at 2048 m (with a washout period of 2 weeks <800m between altitude sojourns). During nights at altitude patients received either NOT (3 l/min) or placebo (ambient air 3 l/min) via nasal cannula according to a randomized cross-over design. Main outcomes were the tricuspid regurgitation pressure gradient (TRPG) measured by echocardiography on the 2nd day at altitude (under ambient air) and various other echocardiographic measures of the right and left heart function. Patients fulfilling predefined safety criteria were withdrawn from the study. Results: Twenty-three COPD-patients (70% GOLD II / 30% GOLD III, mean±SD age 66±5years, FEV1 54±13% predicted) were included in the per-protocol analysis. TRPG significantly increased when patients travelled to altitude (from low altitude 21.7±5.2mmHg to 2048 m placebo 27.4±7.3mmHg and 2048 m NOT 27.8±8.3mmHg) difference between interventions (mean difference 0.4 mmHg, 95%CI -2.1 to 3.0, p = 0.736). The tricuspid annular plane systolic excursion was significantly higher after NOT vs. placebo (2.6±0.6 vs. 2.3±0.4cm, mean difference (95% confidence interval) 0.3 (0.1 to 0.5)cm, p = 0.005). During visits to 2048 m until 24h after descent, eight patients (26%) using placebo and one (4%) using NOT had to be withdrawn because of altitude-related adverse health effects (p < .001). Conclusions: In lowlanders with COPD remaining free of clinically relevant altitude-related adverse health effects, changes in daytime pulmonary hemodynamics during a stay at high altitude were trivial and not modified by NOT.